Pengaruh Peran Keluarga Dan Tenaga Kesehatan Puskesmas Nanggalo Kota Padang Terhadap Kepatuhan Minum Obat Orang Dalam Gangguan Jiwa (ODGJ) - Ramadhanis, Ramadhanis; Lanin, Dasman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of the study was to determine the effect of the role of the family and the role of health workers at the Nanggalo Padang Health Center partially or simultaneously on adherence to drinking ODGJ. This research is using quantitative methods. The population is families and health workers at the Nanggalo Health Center, Padang City. The sample used is 94. The sampling technique is purposive sampling incidental sampling. The research instrument is a questionnaire. Data were analyzed using linear regression and multiple regression. Based on the results of the study, it was found that 1) the family role variable had a positive and significant effect on medication adherence of ODGJ patients with a sig value of 0.000 <0.05. 2) The variable of the role of health workers at the Nanggalo Padang Health Center has a positive and significant influence on medication adherence of ODGJ patients. with a sig value of 0.000 < 0.05. 3) The variables of the family role and the role of health workers at the Nanggalo Padang Health Center simultaneously have a positive and significant effect on medication adherence of ODGJ patients with a sig value of 0.000 <0.05.